Perubahan Pidana dari KUHP Lama ke Baru sebagai Reformasi Penegakan Hukum di Indonesia (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
The enactment of Law Number 1 of 2023 concerning the Criminal Code (KUHP) marks a historic milestone in the reform of Indonesia's criminal law system. This study examines the fundamental changes from the old Criminal Code (Wetboek van Strafrecht) to the new National Criminal Code, focusing on the paradigm shift from retributive justice to restorative justice as a form of law enforcement reform. Using a normative juridical method with a statutory and comparative approach, the study analyzes the philosophical, structural, and substantive transformation embedded in the new Criminal Code. The findings indicate that the new Criminal Code introduces significant reforms including the adoption of the dualistic theory separating criminal acts from criminal liability, the recognition of living law, the expansion of criminal subjects to include corporations, the formulation of sentencing guidelines based on restorative principles, and the integration of Pancasila values as the moral foundation of the criminal law system. The case of corruption prosecution involving the Chromebook laptop procurement at the Ministry of Education illustrates the ongoing challenges of criminal law enforcement during this transitional period. This research concludes that the transition from the old to the new Criminal Code constitutes a comprehensive legal reform that transforms not only normative substance but also the fundamental paradigm of criminal law enforcement in Indonesia